Gender Gaps in Performance: Evidence from Young Lawyers - Ghazala Azmat; Rosa Ferrer (Institute for the Study of Labor (IZA), 2015)
This paper documents and studies the gender gap in performance among associate lawyers in the United States. Unlike other high-skilled professions, the legal profession assesses performance using transparent measures that are widely used and comparable across firms: the number of hours billed to clients and the amount of new client revenue generated. We find clear evidence of a gender gap in annual performance with respect to both measures. Male lawyers bill ten percent more hours and bring in more than twice the new client revenue than do female lawyers. We demonstrate that the differential impact across genders in the presence of young children and differences in aspirations to become a law firm partner account for a large share of the difference in performance. We also show that accounting for performance has important consequences for gender gaps in lawyers' earnings and subsequent promotion. Whereas individual and firm characteristics explain up to 50 percent of the earnings gap, the inclusion of performance measures explains a substantial share of the remainder. Performance measures also explain a sizeable share of the gender gap in promotion.
Keywords: M52; J16; K40; J44; 330; performance measures; gender gaps; high-skilled professionals